Connexins and their channels in inflammation. (1st November 2016) - Willebrords, Joost; Crespo Yanguas, Sara; Maes, Michaël; Decrock, Elke; Wang, Nan; Leybaert, Luc; Kwak, Brenda R.; Green, Colin R.; Cogliati, Bruno; Vinken, Mathieu
Abstract: Inflammation may be caused by a variety of factors and is a hallmark of a plethora of acute and chronic diseases. The purpose of inflammation is to eliminate the initial cell injury trigger, to clear out dead cells from damaged tissue and to initiate tissue regeneration. Despite the wealth of knowledge regarding the involvement of cellular communication in inflammation, studies on the role of connexin-based channels in this process have only begun to emerge in the last few years. In this paper, a state-of-the-art overview of the effects of inflammation on connexin signaling is provided. Vice versa, the involvement of connexins and their channels in inflammation will be discussed by relying on studies that use a variety of experimental tools, such as genetically modified animals, small interfering RNA and connexin-based channel blockers. A better understanding of the importance of connexin signaling in inflammation may open up towards clinical perspectives.